CREATING A CULTURE OF PSYCHOLOGICAL SAFETY: IMPLICATIONS FOR TEAM PERFORMANCE - Kurniawati Ningsih; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This article examines how psychological safety—a shared belief that the team is safe for interpersonal risk-taking—serves as a critical driver of team performance in complex work environments. Through a conceptual analysis of leadership roles, we demonstrate that leaders cultivate this environment by acting as catalysts who frame work as a learning process, models who demonstrate vulnerability through their response to failure and dissent, and enforcers who establish clear norms and equitable structures. The analysis reveals that these behaviors directly enable the learning, innovation, and candid dialogue necessary for high performance by encouraging risk-taking, transforming failures into learning data, and ensuring full team participation. The article concludes that building psychological safety is not a soft skill but a strategic imperative, providing a practical framework for leaders to unlock their team's collective intelligence and build a more adaptive, resilient, and successful organization.